Gravity : A Very Short Introduction - Clifton, Timothy (New York Oxford University Press, 2017)
Gravity is the most immediately familiar of the four fundamental forces of nature, and its effects dominate many of the phenomena commonly observed. Timothy Clifton looks at the development of our understanding of gravity, from Newton's apple to gravitational waves and efforts such as string theory to combine gravity with quantum mechanics
Include Index
Keywords: Gravity -- General relativity (Physics) -- Gravitation